2020
DOI: 10.1515/jpem-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of epicardial adipose tissue thickness on cardiac conduction system in children with type 1 diabetes mellitus

Abstract: ObjectivesInvestigation of the association between epicardial adipose tissue thickness (EATT) and P-wave dispersion (Pd), QT dispersion (QTd), corrected QT dispersion (QTcd) and Tp-e interval in children with Type 1 Diabetes Mellitus (T1DM) was aimed.MethodsForty-one children with T1DM and 41 age- and gender-matched healthy children were included in the study. Demographical characteristics of all cases were examined. In echocardiography; in addition to conventional echocardiographic measurements, end-systolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…In our study, we observed elevated levels of EAT in children with T1D when compared to age, sex, and BMI-matched healthy counterparts. Although studies on this subject in children are limited, the findings were consistent with the studies conducted by Güney et al and Chambers et al 1,2 Although the reason for the increase in epicardial adipose tissue in patients with type 1 diabetes is not fully understood, publications are indicating that this may be related to the insulin dose used, and if the dose used is high or the hba1c is low, this may be related to the high insulin dose. 10,11 On the other hand, it is known that although fat stores are reduced in insulin deficiency, epicardial adipose tissue is protected from this reduction.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, we observed elevated levels of EAT in children with T1D when compared to age, sex, and BMI-matched healthy counterparts. Although studies on this subject in children are limited, the findings were consistent with the studies conducted by Güney et al and Chambers et al 1,2 Although the reason for the increase in epicardial adipose tissue in patients with type 1 diabetes is not fully understood, publications are indicating that this may be related to the insulin dose used, and if the dose used is high or the hba1c is low, this may be related to the high insulin dose. 10,11 On the other hand, it is known that although fat stores are reduced in insulin deficiency, epicardial adipose tissue is protected from this reduction.…”
Section: Discussionsupporting
confidence: 85%
“…It exhibits a strong link to coronary artery disease and has been shown to play a role in the pathophysiology of This comprehensive review aims to elucidate the complex relationship between EAT and T1D in children by exploring the underlying mechanisms and clinical outcomes, metabolic disorders, inflammation, and cardiovascular diseases. 1,2 In epicardial adipose tissue (EAT) assessment, echocardiography is extensively used due to its widespread availability and noninvasive nature. However, this method grapples with significant limitations, including variability between operators and within the same operator's repeated measurements, alongside an inherent incapacity to accurately gauge EAT volume or delineate specific regional distributions of EAT, such as peri-atrial and pericoronary areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, these parameters were similar between the values obtained at the third ECG and controls. In the study of Güney et al ( 26 ), all patients with T1DM were previously diagnosed, whereas our patient group was composed of more than half newly diagnosed T1DM. Additionally, there was no significant difference in regard to Tp-e/QTc in our study.…”
Section: Discussionmentioning
confidence: 82%
“…Inanır et al ( 32 ) reported these parameters to be increased in adults with T1DM compared to their control group, whereas in another study, these ECG parameters were found to be similar between T1DM patients and controls ( 37 ). In the study of Güney et al ( 26 ), conducted in children with T1DM, Tp-e was increased compared to the control group, but Tp-e/QT and Tp-e/QTc ratios were similar with healthy controls. We could not find any data in the literature about Tp-e, Tp-e/QT or Tp-e/QTc in ​​a pediatric population with DKA.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation